2018
DOI: 10.1111/acer.13830
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Inhibitory Subcomponents Associated with Changes in Binge Drinking Behavior: A 6‐Month Longitudinal Design

Abstract: The results suggest that the cancellation of a prepotent response, as opposed to the withholding of response or interference inhibition, is a more sensitive inhibitory measure associated with increases in binge drinking behavior among female young adult college students. Further exploration of inhibitory subcomponents relative to substance use is greatly needed (e.g., more extensive longitudinal designs and neuroimaging techniques).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…Impairment of the inhibitory executive function has been associated with a variety of negative outcomes across the lifespan. For example, decreased inhibition has been correlated with poorer math and reading comprehension skills in children (e.g., St. Clair‐Thompson & Gathercole, ), procrastination and alcohol abuse in college‐aged adults (e.g., Paz, Rosselli, & Conniff, ; Rebetez, Rochat, Barsics, & Van der Linden, ), and aggression in adults (e.g., Hoaken, Shaughnessy, & Pihl, ).…”
Section: Executive Functionsmentioning
confidence: 99%
“…Impairment of the inhibitory executive function has been associated with a variety of negative outcomes across the lifespan. For example, decreased inhibition has been correlated with poorer math and reading comprehension skills in children (e.g., St. Clair‐Thompson & Gathercole, ), procrastination and alcohol abuse in college‐aged adults (e.g., Paz, Rosselli, & Conniff, ; Rebetez, Rochat, Barsics, & Van der Linden, ), and aggression in adults (e.g., Hoaken, Shaughnessy, & Pihl, ).…”
Section: Executive Functionsmentioning
confidence: 99%
“…A higher rate of commission error and prolonged stop-signal reaction times with intact go reaction time have been observed previously in adults with ADHD ( 47 ), and are also considered as deficits in inhibitory control in individuals with substance use disorder ( 48 ). While some imaging studies did not observe significant group differences on the behavioral level [e.g., ( 39 , 40 )], others reported a correlation between stop-signal reaction times and stopping an initiated response, and binge drinking behavior ( 49 ). It has also been suggested that deficits in task performance in individuals with AUD, e.g., an increase in omission errors and no change in reaction times ( 48 ), might not only be due to deficits in response inhibition but also due to problems related to discrimination ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings indicate that later components of response inhibition should be assessed (e.g., by using a Stop-Signal task) when examining consequences of impaired response inhibition or administering preclinical screening measures. It was observed in young heavy drinkers that only deficits in action cancellation were related to an increase in binge drinking in females ( 49 ). While interference inhibition did not result in significant observations when comparing clinical populations to healthy controls, directly contrasting ADHD and AUD led to significant observations in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, they believe that binge drinking is socially acceptable at that age ( Sudhinaraset et al, 2016 ), rendering them unaware that their drinking may be problematic, or that it even impacts their cognitive functioning or self-control ( Bishop and Rodriquez Orjuela, 2018 , Probst et al, 2015 ). And yet, inhibition failures on tasks probing inhibitory control are predictive of an escalation in binge drinking, AUD severity ( Clark et al, 2017 , Claus et al, 2013 , Nigg et al, 2006 , Paz et al, 2016 , Paz et al, 2018 ), as well as relapse in cocaine dependence ( Luo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%